The Impact of Sudden Commencements on Ground Magnetic Field Variability: Immediate and Delayed Consequences - Andrew W. Smith; Colin Forsyth; Jonathan Rae; Craig J. Rodger; Mervyn P. Freeman (Space Weather)
Abstract We examine how Sudden Commencements (SCs) and Storm Sudden Commencements (SSCs) influence the occurrence of high rates of change of the magnetic field (R) as a function of geomagnetic latitude. These rapid, high amplitude variations in the ground‐level geomagnetic field pose a significant risk to ground infrastructure, such as power networks, as the drivers of geomagnetically induced currents. We find that rates of change of ∼30 nT min−1 at near‐equatorial stations are up to 700 times more likely in an SC than in any random interval. This factor decreases with geomagnetic latitude such that rates of change around 30 nT min−1 are only up to 10 times more likely by 65°. At equatorial latitudes we find that 25% of all R in excess of 50 nT min−1 occurs during SCs. This percentage also decreases with geomagnetic latitude, reaching ≤1% by 55°. However, the time period from the SC to 3 days afterward accounts for ≥90% of geomagnetic field fluctuations over 50 nT min−1, up to ∼60° latitude. Above 60°, other phenomena such as isolated substorms account for the majority of large R. Furthermore, the elevated rates of change observed during and after SCs are solely due to those classified as SSCs. These results show that SSCs are the predominant risk events for large R at mid and low latitudes, but that the risk from the SC itself decreases with latitude.